Islamic perspective on human nature - Abdul Razak, Mohd Abbas; Mustapha, Maziah (IIUM Press, 2025)
Human nature is a widely and popularly discussed topic not only in the East but also in the West. This topic has drawn people from diverse backgrounds of knowledge to explore and investigate who or what man is in relationship to his Creator and other creations that exist in the universe. The research on man and the attempts to answer many of the intricate questions related to his creation and existence which started in the ancient past is still ongoing. The fact that the latest findings on man have added information to the existing body of knowledge makes the study of human nature a dynamic and perennial one. Within the scope of this chapter, the researchers have attempted to discuss the topic of human nature from the Islamic perspective. In discussing the nature of man, the researchers have ventured into the physical and metaphysical realms of his existence as described in the Qur’an. Besides that, the researchers have also entertained some discussions on how man has been perceived in mainstream Western and Islamic psychologies. In concluding the chapter, the researchers have anchored the discussion as to why the study of human nature is important.